Formulasi Dan Evaluasi Sediaan Fisik Krim Antioskidan Ekstrak Pelepah Pohon Aren (Arenga Pinnata Merr.) - Iqbal Abdul Raup; Gina Septiani Agustien; Nitya Nurul Fadilah (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Aren (Arenga pinnata Merr.) is a biological resource that is thought to have antioxidant abilities and is easily found in all regions of Indonesia. The stem is used for traditional medicine to relieve itching and scars on the skin. The aim of this study was to find out whether palm frond extract (Arenga pinnata Merr.) can be formulated into a cream and has good quality. The research method used is experimental in nature by formulating the extract into three formulations namely extract concentrations of 1%, 2%, 3%. Data analysis was carried out using qualitative analysis including organoleptic tests, homogeneity tests, and quantitative analysis including pH tests, spreadability tests, adhesion tests, viscosity and using One Away ANOVA statistics. The results of the analysis showed that there was no significant difference in the concentration of palm frond cream on pH with a sig. value of 0.279 (sig. > 0.05), adhesion of 0.544 (sig. > 0.05) and viscosity that met the standard of good cream viscosity, namely between (2000 - 50000 cps). Analysis of the research data shows that the three variations of the extract can be formulated in cream preparations and have standard quality cream preparations that meet the requirements, there is no effect of variations in the concentration of palm fronds extract. The test results of the antioxidant activity of palm tree fronds that have been carried out show that in Formulas I, II, and III the IC50 values ​​were 8.88 µg/mL, 9.89 µg/mL, 6.83 µg/mL and vitamin C had a IC50 of 0.726 µg/mL. The best antioxidant content was found in formulation III with an IC50 value of 6.83 µg/mL.